Knowledge, attitudes, and practices of government workers on zoonotic parasites in pet animals: a study in Central Gondar Zone, Ethiopia - Adanie Delie; Gashaw Getaneh Dagnaw; Abebe Tesfaye Gessese; Haileyesus Dejene (BMC, 2024)
Abstract Background Parasitic zoonoses are infections transmitted between vertebrate animals and humans, posing serious public health risks and significant economic consequences. The study aimed at assessing government workers' knowledge, attitudes, and practices (KAP) regarding zoonotic parasites of pet animals in Ethiopia's central Gondar zone. Methods A cross-sectional study was carried out in selected towns of Central Gondar Zone, Northwest Ethiopia from January 2022 to August 2022. Four hundred randomly selected government employees participated in the study. Data were collected through semi-structured questionnaire administered by face-to-face interview. The chi-squared (χ2) was calculated for association and p-value less than 0.05 was considered as significant. Results A 57.25% of respondents were males and 42.75% were females. Most of the respondents, 67.5%, had completed college/university education. About 60% of the respondents had 'high knowledge', 57.25% had 'positive attitude', and 73% had 'good practice' regarding pet animals as a source of zoonotic parasites. The chi-square analysis revealed a significant discrepancy (p < 0.05) between knowledge with sex, educational level, and position in the house. The attitude level was significantly associated (p < 0.05) with educational level, religious view, and service year. Significant association was also observed (p < 0.05) between practice level of the respondents and educational level and marital status. The study also showed a significant association between knowledge and attitude (χ2 = 40.4, p ≤ 0.001), knowledge and practice (χ2 = 34.9, p ≤ 0.001), and attitude and practice (χ2 = 12.76, p = 0.013) of the respondents. Conclusion Although our results revealed that more than half of the participants had good knowledge, attitudes, and practices regarding zoonotic parasites of pet animals, enhanced routine hygienic practices and regular awareness creation programs are recommended to bridge existing gaps.